The relationship between stroke parameters and physiological responses at the varios swim speeds - Nomura, T.; Shimoyama, Y. (Biomechanics and Medicine in Swimming IX, 2003)
PURPOSE: Present study was to investigate the relationship between stroke parameters and physiological responses, furthermore aim to find the best fitted swim speed at competition. METHOD: The subjects were 23 highly trained versity swimmers (Freestyle: n=12, Backstroke: n=3, Breaststroke: n=4, Butterfly stroke: n=4). Progressive swim tests were conducted using swim flume. Each test consisted of 3 min swim and 3 min rest. Swimmers were instructed to swim from 50 % of maximum speed (200m best record), and increased 5 % at each trial up to volitional effort. Stroke rate (SR) and Stroke length (SL) were measured at each speed using video camera (EVI-D30, Sony Inc.). Blood lactate was measured at the end of each swim and determined OBLA and LT. RESULTS: SR increased exponentially with increased swim speed in all strokes. SL increased with swim speed but started to decrease at the speed of 65-70 % of 200 m best record (Stroke Length Peak Point; SLPP) in all freestylers. This speed was well corresponded to OBLA and LT, respectively. However, the SLPP were not observed in other strokes (Backstroke, Breaststroke, Butterfly stroke) because individual differences were seen in the stroke characteristic of swimmers. Further investigation is needed to clarify the relationship stroke parameter (SR, SL) and physiological responses of other strokes. The SLPP was highly correlated with endurance capacity such as OBLA and LT. Present findings suggested that SLPP would be corresponding to efficient and faster speed during training. Furthermore, from the results above, we could apply the non invasive SLPP data to OBLA training.